Detection of plasmid-mediated colistin-resistance genes in Enterobacteriaceae isolates from food-producing animals and meat. Identification of the novel variant mcr-3, Portugal, 2010-2015. - Clemente, L. (2018)
Following the original report of plasmid-mediated colistin resistance (PMCR) in China, several studies in different countries reported a worldwide distribution of the mcr-1 gene in Enterobacteriaceae. A novel variant, mcr-2, was also detected in colistin-resistant Escherichia coli isolates, from sick calves and piglets in Belgium; since that several other mcr-1 variants has been identified. In this study, we analysed colistin-resistant E. coli and Salmonella enterica isolates from different animal origins, for the presence of PMCR encoding genes. Thus, our aim was to understand the extension of the problem of colistin resistance and PMCR, as colistin is the last resort to treat human infections caused by Gram negative bacteria resistant to all antibiotics, namely carbapenems.